One pot synthesis and characterization of Fe3O4 Nanorod-PNIPA Nanogel Composite for protein adsorption - Rajar, Kausar; Karakus, Baris.; Koc, Kenan; Alveroglu, Esra (ELSEVIER SCIENCE BV, 2016)
In this study, Fe3O4 Nanorod-PNIPA Nanogel Composite nanomaterial is synthesized, characterized and used for lysozyme adsorption. XRD, ATR-FTIR, AFM and SEM measurements reveal that nanorods-nanogels composite was prepared successfully. The diameter of nanorods and the average particle size of nanogels are found around 150 nm and 300 nm, respectively. VSM measurement shows that the Fe3O4 particles are in rod shape and has superparamagnetic behavior, no hysteresis and remnant is detected. The adsorption kinetic of lysozyme on composite material is studied via fluorescence method, and the adsorption reaction rate constant is calculated as 0.904 s(-1) by using Langmuir-Hinshelwood pseudo second order model. Fe3O4 Nanorod-PNIPA Nanogel Composite is appeared as a fast catalyst for lysozyme like protein immobilization. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Gel; Nanorod; Magnetism; Polymer; Adsorption; Fluorescence; DRUG-DELIVERY; MAGNETITE NANOPARTICLES; BIOMEDICAL APPLICATIONS; CONFORMATIONAL-CHANGES; HYDROGELS; NANOCOMPOSITES; LYSOZYME; POLYMERIZATION; MICROEMULSION; ASSEMBLIES; Materials Science